Expectation of Selfishness From Others in Borderline Personality Disorder - Lévay, Erika Evelyn; Bajzát, Bettina; Unoka, Zsolt Szabolcs (Frontiers in Psychology, 2021)
Social difficulties are apparent in borderline personality disorder (BPD). Behavior in BPD is characterized by mistrust and expectations of malevolence from others. We examined whether there is an asymmetry between their social behavior and their belief about other people's social motivations. Subjects completed a task where they had to allocate money between themselves and an imagined other they will not meet and interact with. In addition they also had to report their expectations about how the imagined other would solve the task. We hypothesized that even though BPD patients will act in a prosocial way, they will expect selfish behavior from the other. We used the Slider Measure of social value orientation (SVO) and also created a modified version of the measure to examine the discrepancy between the subjects' own SVO and their expectations from other people. We compared the results of thirty clinically diagnosed borderline BPD patients to a matched sample of healthy participants. Our results show that the BPD group's selfishness expectations significantly outweigh the expectations of selfishness in the HC group (U = 269, p = .007). This result further supports the mistrust and negativity bias observed in various aspects of social interactions in BPD.